Retention in care among people living with HIV in the national antiretroviral therapy programme in Guinea: A retrospective cohort analysis. - Kadio Jean-Jacques Olivier Kadio; Cissé Amadou; Saidou Diallo Thierno; Foromo Guilavogui; Fapeingou Tounkara Adrien; Pe Damey; Sow Alhassane; Fily Bah Fatoumata; Sékou Youla Souleymane; Diallo Ibrahima; Nestor Leno Niouma; Mboungou Lazare; et al. (Public Library of Science (PLoS), 2023)
Few studies have investigated retention in HIV care in West Africa. We measured retention in antiretroviral therapy (ART) programmes among people living with HIV and re-engagement in care among those lost to follow up (LTFU) in Guinea and identified associated risk factors using survival analysis. Patient-level data were analysed from 73 ART sites. Treatment interruptions and LTFU were defined as missing a ART refill appointment by over 30 days and by over 90 days respectively. A total of 26,290 patients initiating ART between January 2018 and September 2020 were included in the analysis. The mean age at ART initiation was of 36.2 years, with women accounting for 67% of the cohort. Retention 12 months after ART initiation was 48.7% (95%CI 48.1-49.4%). The LTFU rate was 54.5 per 1000 person-months (95% CI 53.6-55.4), with the peak hazards of LTFU occurring after the first visit and decreasing steadily over time. In an adjusted analysis, the hazards of LTFU were higher among men compared to women (aHR = 1.10; 95%CI 1.08-1.12), being aged 13-25 years old versus older patients (aHR = 1.07; 95%CI = 1.03-1.13), and among those initating ART in smaller health facilities (aHR = 1.52; 95%CI 1.45-1.60). Among 14,683 patients with an LTFU event, 4,896 (33.3%) re-engaged in care, of whom 76% did so within six months from LTFU. The re-engagement rate was 27.1 per 1000 person-months (95%CI 26.3-27.9). Treatment interruptions were correlated with rainfall patterns and end of year mobility patterns. Rates of retention and re-engagement in care are very low in Guinea, undermining the effectiveness and durability of first-line ART regimens. Tracing interventions and differentiated service delivery of ART, including multi-month dispensing may improve care engagement, especially in rural areas. Further research should investigate social and health systems barriers to retention in care.